Tribological study on the biodiesel produced from waste cooking oil, waste cooking oil blend with Calophyllum inophyllum and its diesel blends on lubricant oil - Jassinnee Milano; Abdul Halim Shamsuddin; A.S. Silitonga; A.H. Sebayang; Munawar Alfansury Siregar; H.H. Masjuki; Muhammad Anhar Pulungan; Shir Reen Chia; M.F.M.A. Zamri (Energy Reports, 2022)
Biodiesel or biodiesel–diesel fuel is the current fuel used to power transportation engines. Contamination on lubricating oil is a common issue due to leakage or extensive use of engines. This study explores the lubricant oil blend’s friction and wear with the biodiesel derived from waste cooking oil, waste cooking oil blend withCalophyllum inophyllum oil, and biodiesel–diesel​ blend. The blending of biodiesels and biodiesel–diesel blend with lubricant oil varies from 5% to 25% of biodiesels and biodiesel–diesel with 95% to 75% of lubricating oil based on volume ratio. The test was conducted using a four-ball tribotester according to the ASTM D 4172. The result showed that blending of BWCIL75 with biodiesel–diesel has the lowest friction coefficient (0.072) among tested oil. The wear scar on the ball bearing lubricated with the blending mixture showed an acceptable diameter value. The wear morphology has shown that a worn surface with black spots provides more protection to the tested ball. The result found that fatty acid contained in the biodiesel and the low viscosity of biodiesel significantly reduced the frictional coefficient of the lubricating oil and worked as wear prevention. Mechanical efficiency of machinery component favour low coefficient of friction. This study indicated that biodiesel produced from waste cooking oil blended with Calophyllum inophyllum oil shows better lubricity and can be used as an additive to petroleum-based lubricant for better automotive engine performance.